Isolation and characterization of farm pig adipose tissue-derived mesenchymal stromal/stem cells - Garcia,G.A. (2022)
Adipose tissue-derived mesenchymal stromal/stem cells (ASCs) are considered important tools in regenerative medicine and are being tested in several clinical studies. Porcine models are frequently used to obtain adipose tissue, due to the abundance of material and because they have immunological and physiological similarities with humans. However, it is essential to understand the effects and safe application of ASCs from pigs (pASCs) as an alternative therapy for diseases. Although minipigs are easy-to-handle animals that require less food and space, acquiring and maintaining them in a bioterium can be costly. Thus, we present a protocol for the isolation and proliferation of ASCs isolated from adipose tissue of farm pigs. Adipose tissue samples were extracted from the abdominal region of the animals. Because the pigs were not raised in a controlled environment, such as a bioterium, it was necessary to carry out rigorous procedures for disinfection. After this procedure, cells were isolated by mechanical dissociation and enzymatic digestion. A proliferation curve was performed and used to calculate the doubling time of the population. The characterization of pASCs was performed by immunophenotyping and cell differentiation in osteogenic and adipogenic lineages. The described method was efficient for the isolation and cultivation of pASCs, maintaining cellular attributes, such as surface antigens and multipotential differentiation during in vitro proliferation. This protocol presents the isolation and cultivation of ASCs from farm pig as an alternative for the isolation and cultivation of ASCs from minipigs, which require strictly controlled maintenance conditions and a more expensive process.